Analisis Ayat Keimanan dalam Al-Qur'an Perspektif Tafsir Salman - Fadhila, Nurul; Wirman, Eka Putra; Zulbadri, Zulbadri (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
This research is a descriptive qualitative research using a library research model which examines the analysis of the review of the verses of faith in Tafsir Salman. It can be concluded from this research that the interpretation of the verses of faith in Salman's Tafsir focuses more on the three surahs found in juz amma, namely surah Al-Ikhlas, Al-Falaq and Al-Naas. Surah al-Ikhl?sh is related to monotheism rub?biyah and monotheism asm?' wa al- characteristic, the manifestation of the value of monotheism in this surah is: Allah is Ahad and Allah is al-Shamad. In Surah al-Falaq related to the manifestation of monotheism ul?hiyah, namely: prayer as a protector from anxiety and His creation, zakat as a protector from stinginess and envy, fasting is a protector from haste and the evils of the night, and pilgrimage is a protector from complaints and evil magic. Whereas in Surah al-N?s related to monotheism ul?hiyah, the points of embodiment of the value of monotheism which are illustrated in sura al-N?s are: al-mu'awwizatain the source of strength, and the creed as an antidote to anxiety in human shadr